The Impact of Implication Problem Posing Learning Model on Students in High Schools - Suarlin, Suarlin; Negi, Surabhi; Ali, Muhammad Ichsan; Bhat, Bilal Ahmad; Elpisah, Elpisah (Three E Science Institute, 2021)
Problem posing is a learning model that requires students to compose their questions or solve a problem into more straightforward questions that refer to solving the problem based on the initial situation. The study aimed to determine the increase of students in mastering the learning material through the Problem Prosing Learning Model. The type of research used in this study is quasi-experimental research. The sample used was 64 high school students with mathematics as the learning subject. There are two class groups: the experimental class with 31 students and the control class with 33 students. The research data obtained were processed by analysis of the paired sample t-test. The research results found that learning with the problem-posing approach made students active and creative, as seen from the ability of students to develop their questions based on the information provided. Students can process and explore existing information and ask problems or questions that can be resolved. Learning with the problem-posing approach can also increase student activity in the learning process, especially in interacting and sharing ideas with other students and with the teacher. Learning activities are meaningful, and student understanding of the concept becomes better.